Woodcarving motifs of verandah and covered porch at Melaka traditional houses / Farah Wahidah Gazali, Arba'iyah Ab. Aziz and Norwani Md Nawawi - Gazali, Farah Wahidah; Ab. Aziz, Arba'iyah; Md Nawawi, Norwani (Universiti Teknologi MARA, 2018)
Woodcarving is a traditional significant art to the Malay architecture in Malaysia. Malay traditional houses becomes a symbol of ancient craftsmanship skills which having beautiful architecture and richness of ornamentation. Nowadays, traditional houses at Melaka become hard to find. The documentation of knowledge about woodcarving motifs should be made and exposed to younger generations as well as a valuable collection of traditional Malay heritage. The structure of Melaka houses is made up of covered porch, verandah, the main house, the central section and the kitchen. This paper intends to focus more detail about woodcarving at verandah and covered porch at entrance of the house. The houses have been selecting are Rumah Yusof Awal, Rumah Hashim Tahar, Rumah Wahab Arshad and Rumah Demang Ghani. This research uses qualitative method as a way to understand motif of woodcarving at Melaka traditional houses. Data collection of motifs will be depending at field studies at houses through photography and sketches on site. This research also will use theory Zakaria Ali to interpret and analyzing of woodcarvings motifs. In design perspective, the findings would serve in understanding the visual attributes of woodcarving such as motifs and design forms. The paper would fill in the gap of new knowledge regarding the motif woodcarving at Melaka traditional houses.